2012 7th International Symposium on Software Engineering for Adaptive and Self-Managing Systems (SEAMS) 2012
DOI: 10.1109/seams.2012.6224401
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing dynamically updating controllers from changes in scenario-based specifications

Abstract: Many software-intensive systems are expected to run continuously while their environments change and their requirements evolve, so their implementation must be updated dynamically to satisfy changing requirements while coping with changing environment properties. Techniques for developing dynamically updating systems exist, but thus far almost no attention has been paid to defining when updates are correct with respect to a changing specification, i.e., when a system can safely disregard its current obligation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Based on their definition, they claimed that in the example of the RailCab system it is too late to apply an update when the RailCab is at the lastEmergencyBrake section because the RailCab cannot starts the second communication with the controller after update takes place and hence cannot know the status of the crossing status [24]. This coincides with our second counterexample in Section V-C.…”
Section: Related Worksupporting
confidence: 69%
See 2 more Smart Citations
“…Based on their definition, they claimed that in the example of the RailCab system it is too late to apply an update when the RailCab is at the lastEmergencyBrake section because the RailCab cannot starts the second communication with the controller after update takes place and hence cannot know the status of the crossing status [24]. This coincides with our second counterexample in Section V-C.…”
Section: Related Worksupporting
confidence: 69%
“…It has been observed that the mechanism may cause problems [24]. Suppose that the controller fails to close the gate Fig.…”
Section: A a Buggy Railcab Crossing Mechanism And A Fixed Versionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the model is updated dynamically at runtime. In [GGM12], the aim is introducing safe and automatic self-adaptation mechanisms driven by the requirement and environment changes. In this research, the system is controlled by a controller that enforces requirements and environment assumptions.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, Whittle et al [25,26] have proposed RELAX, which supports a fuzzy logic-based approach to analyzing uncertainty in adaptive systems. Ghezzi et al [5] have examined the problem of when to introduce a new controller to a running system without restarting it, and verifying that the new controller meets its speciication. Souza et al [23] have proposed a method for weakening requirements as a way to adapt to the changing context.…”
Section: Introductionmentioning
confidence: 99%